2020
DOI: 10.1016/j.celrep.2020.107919
|View full text |Cite
|
Sign up to set email alerts
|

A Neural System that Represents the Association of Odors with Rewarded Outcomes and Promotes Behavioral Engagement

Abstract: Highlights d Ensembles from both the OT and pPCX accurately encode conditioned odors d More OT neurons represent rewarded odors and do so in manners different from pPCX d OT D1 neurons flexibly represent rewarded odors during reversal learning d Activation of OT D1 neurons promotes engagement in a reinforcer-motivated task

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 65 publications
(126 reference statements)
2
36
1
Order By: Relevance
“…Firing rate differences in a subset of cells emerged just before the odor port exit during which mice performed behavioral choices ( Figure 5 ). These features resembled the response pattern for learned odor-guided tasks observed in the piriform cortex ( Gadziola et al, 2020 ; Gire et al, 2013 ). However, many vTT cells increased their firing rate before the odor presentation ( Figures 1D , 2B and 4B ), and individual vTT cells exhibited a particular tuning pattern characterized by peak tuning and tuning duration.…”
Section: Discussionsupporting
confidence: 65%
“…Firing rate differences in a subset of cells emerged just before the odor port exit during which mice performed behavioral choices ( Figure 5 ). These features resembled the response pattern for learned odor-guided tasks observed in the piriform cortex ( Gadziola et al, 2020 ; Gire et al, 2013 ). However, many vTT cells increased their firing rate before the odor presentation ( Figures 1D , 2B and 4B ), and individual vTT cells exhibited a particular tuning pattern characterized by peak tuning and tuning duration.…”
Section: Discussionsupporting
confidence: 65%
“…These findings suggest that the spatial pattern of neural activation in the OT encodes odor-induced attractive or aversive behaviors, in contrast to the odor map of the olfactory bulb. Consistent with this, electrophysiological recordings in behaving mice revealed that the firing activity of the OT flexibly encoded the valence of conditioned odors over odorant identity (Gadziola et al, 2015(Gadziola et al, , 2020. These studies suggest that OT neurons evaluate odorants in an experience-dependent manner and that spatially segregated domains and neuronal subtypes play distinct roles in inducing appropriate motivated behaviors.…”
Section: Functional Domains Of the Olfactory Tubercle And Odor-guidedsupporting
confidence: 57%
“…These connections provide ways which bring the olfactory input into close involvement with areas generating learning, emotion and olfactory-guided behavior. Of special interest is evidence showing direct connections of the tufted cells to the olfactory tubercle (Nagayama et al, 2010), and the role of the tubercle in olfactory-guided reward behavior (Gadziola et al, 2020). Given these multiple types of output, much of the olfactory cortex must reflect an organization of the olfactory input that can be sent to these distinct roles in these differing output systems.…”
Section: Output From the Posterior Olfactory Cortexmentioning
confidence: 99%